SOCIAL MEDIA PLATFORM AS A MAINSTREAM NEWS IN KERALA: A CASE STUDY ON INSTAGRAM AS A SOCIAL MEDIA PLATFORM - Suresh, Akshaya; George, Neenu; C, Karthika (International Journal of Psychosocial Rehabilitation, 2020)
Social media has now a days become a more relevant platform for incessant communication. Compared to other print and traditional media, users tend to take social media as a major platform to put in their views and see to very often to discuss news. Visual-based networks such as Instagram now play a major role in linking and international audience beyond traditional language barriers to one virtual space. In our study we will be looking into deep aspects of social media platform – INSTAGRAM as a rising news platform, and how news is depicted or portrayed on Instagram confined to the region Kerala. Also we will be looking into the amount of reach and impact it has on the users. The main purpose of this study is to examine the idea of users regarding Instagram as a news portal and to know the potential of Instagram as a news platform in India. By this study we will analyse the consumption of the users of Instagram as a news platform. The methods used in the study are quantitative method and theoretical analysis. The data was collected by a structured questionnaire distributed through internet media platforms with the use of Google forms. Responses were collected from 368 samples using Simple Random Sampling. New media is growing gradually as a journalistic platform. So it becomes relevant for media students to analyse and understand the potential of various social media platforms as a news platform and research on the change in behavioural habits of the users regarding the same